“I have no milk!” : The myths and realities of breastmilk production - Jahn Kassim, Puteri Shanaz; Jamani, Nurjasmine Aida (The Malaysian Medical Gazette, 2018)
Every mother who has given birth will be able to relate the magical moment of breastfeeding her newborn. It is the moment when she feels fulfilled as a mother, and the immense joy of love as the baby sucks in every drop of the precious breast milk. The first few days after your baby is born, it is definitely the period of tremendous change of your life. You feed your baby every few hours, each time he or she demands for it. The “immense joy” may be replaced with an ‘overwhelming’ feeling in the next few days after birth: you could hardly rest or sleep as the baby cries to be fed every few hours, and even at night. At this time, these thoughts may cross your mind: